2018
DOI: 10.1039/c8tc00452h
|View full text |Cite
|
Sign up to set email alerts
|

Significantly enhanced and precisely modeled thermal conductivity in polyimide nanocomposites with chemically modified graphene via in situ polymerization and electrospinning-hot press technology

Abstract: Significantly improved thermal conductivities and a more accurate thermal conductivity model were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 389 publications
(177 citation statements)
references
References 86 publications
1
174
0
2
Order By: Relevance
“…the fillers were randomly oriented completely. For such a case, Guo et al have recently reported a scheme to convert the three components of anisotropic thermal conductivity ( Keff,11,Keff,22, and Keff,33) into an overall isotropic thermal conductivity ( K′ ). This scheme was derived from plane source method for measuring the thermal conductivity and therefore only suitable for the particular measurement method.…”
Section: Calibration and Validation Of The Modelmentioning
confidence: 99%
“…the fillers were randomly oriented completely. For such a case, Guo et al have recently reported a scheme to convert the three components of anisotropic thermal conductivity ( Keff,11,Keff,22, and Keff,33) into an overall isotropic thermal conductivity ( K′ ). This scheme was derived from plane source method for measuring the thermal conductivity and therefore only suitable for the particular measurement method.…”
Section: Calibration and Validation Of The Modelmentioning
confidence: 99%
“…Multiscale CFs grafted with PVA or PEG were used as the base material for the synthesis of the PVA/ CF /epoxy and PEG/ CF /epoxy resin hybrid composites by compression molding. The epoxy resin and hardener H‐256 (weight ratio 100: 32) were mixed and stirred for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…[50] Taking spherical nanoparticles reinforced ICPs for an example, Figure 3 illustrates the fabrication of core-shell structured conductive PNCs using in situ chemical polymerization. [50] Taking spherical nanoparticles reinforced ICPs for an example, Figure 3 illustrates the fabrication of core-shell structured conductive PNCs using in situ chemical polymerization.…”
Section: In Situ Polymerizationmentioning
confidence: 99%